Relationship Risk Factors and Laten Tuberculosis Infection (LTBI) in HIV Patients - Irwandi, Delvan; Harsini, Harsini; Reviono, Reviono (Jurnal Respirologi Indonesia, 2019)
Introduction: In 2014 globally 9.6 million people are infected with TB, including 1.2 million people living with HIV. HIV positive patients have a risk of Tuberculosis (TB), infection or latent TB infection (LTBI) about 5-8% per year and the risk of developing active TB 3 times higher than the immunocompetent individuals. The impact of HIV infection on the immune system is the destruction of lymphocyte T CD4 and declining nutritional status. Nutritional status can be assessed by clinical signs, anthropometry and biochemical indicators such as serum albumin levels. Methods: Cross-sectional observational epidemiological research in RS Dr. Moewardi, Surakarta, to patients with HIV, from April to May 2017 to observe the association of risk factors with LTBI in HIV patients. The first step is patient and family anamnesis, history of past and family illness, duration of antiretroviral therapy, Cluster of Differentiation 4 (CD4) count, BMI count, serum albumin concentration, immunologic Tuberculin Skin Test (TST) for LTBI diagnosis. Results: Total of 93 people meet the criteria. There was no association close contact history with active tuberculosis patients with ITBL in HIV (p = 0.5, OR 1.268; 95% CI 1.139-1.411); no association of BMI classification with LTBI in HIV (P=1.000; OR=0.894; 95%CI=0.326-2.457), no association of serum albumin grade with ITBL in HIV (P=0.19; OR=1.284; 95%CI=1.147-1.436); there was a significant association of CD4 classification with LTBI in HIV (P=0.033; OR=3.560; 95%CI=1.214-10.433), there was no association between duration of antiretroviral therapy with LTBI in HIV (P=0.636; OR=0.969; 95% CI=0.244-3.848). Conclusions: HIV patients with advanced CD4 and severe immunosuppressive CD4 classification (CD4+